1993
DOI: 10.1093/ajcn/58.5.754s
|View full text |Cite
|
Sign up to set email alerts
|

Intermediary metabolism of fructose

Abstract: Most of the metabolic effects of fructose are due to its rapid utilization by the liver and it by-passing the phosphofructokinase regulatory step in glycolysis, leading to far reaching consequences to carbohydrate and lipid metabolism. These consequences include immediate hepatic increases in pyruvate and lactate production, activation of pyruvate dehydrogenase, and a shift in balance from oxidation to esterification of nonesterified fatty acids, resulting in increased secretion of very-low-density-lipoprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
518
2
21

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 598 publications
(577 citation statements)
references
References 96 publications
19
518
2
21
Order By: Relevance
“…Western blotting revealed that fructokinase was detected in the liver and kidney as expected (Mayes, 1993), but was absent from the brain (Figure 7). However, fructokinase was detected in the optic nerve, although at a lower density than in liver or kidney.…”
Section: Fructokinase Expression In Optic Nervesupporting
confidence: 53%
See 1 more Smart Citation
“…Western blotting revealed that fructokinase was detected in the liver and kidney as expected (Mayes, 1993), but was absent from the brain (Figure 7). However, fructokinase was detected in the optic nerve, although at a lower density than in liver or kidney.…”
Section: Fructokinase Expression In Optic Nervesupporting
confidence: 53%
“…Thus, hexokinase in both the brain and MON displays a low K m with glucose as substrate, but orders of magnitude higher for fructose. That fructokinase, which does not phosphorylate glucose (Mayes, 1993), is present in the MON is a surprise, especially given its absence in the cortex, and its absence from cultured astrocytes, although these were of cortical origin (Bergbauer et al, 1996). Its low K m and high V max , similar to the values in liver (Hagopian et al, 2005), suggest that if any fructose is metabolised in the MON, it will be via fructokinase and not hexokinase.…”
Section: Fructose Metabolismmentioning
confidence: 99%
“…In that, fructose differs from glucose, because the ADP and citrate concentrations exert a negative feedback control on the initial steps of glycolysis. As a consequence of this absence of feedback inhibition, virtually all the fructose ingested with a meal (whether under its pure, unbound form, or bound to glucose in sucrose) is rapidly converted into hepatic triose-phosphates [11]. These substrates are subsequently oxidized within the liver cells or converted into glucose and lactate to be released into the bloodstream, or converted into hepatic glycogen.…”
mentioning
confidence: 99%
“…At low intakes, fructose has beneficial effects on glucose disposal by increasing glucose uptake via an increased translocation of glucokinase from the inactive-nuclear form to the cytosolicactive form (VanSchaftingen et al, 1997). However, an excess of fructose floods the glycolytic pathway with lipogenic precursors (glycerol-3-phosphate, acetyl-co-A) by bypassing the regulated step in the pathway catalysed by the enzyme phosphofructokinase (Underwood and Newsholme, 1965;Mayes, 1993). Fructose increases the production of lactate by an increased conversion of pyruvate by the enzyme lactic dehydrogenase (Sahebjami and Scalettar, 1971).…”
Section: Fructose and Metabolic Flexibilitymentioning
confidence: 99%
“…The increased availability of lipogenic and gluconeogenic molecules (pyruvate, glycerol phosphate, acetyl-co-A, lactate and fatty acids), lipogenesis activators (sterol receptor element binding protein 1C) and gluconeogenesis activators (sirtuin 1) induce an insulin-independent increase in de novo hepatic lipogenesis and gluconeogenesis, a metabolic effect observed during fructose supplementation experiments in animals (Noguchi and Tanaka, 1995;Commerford et al, 2002;Matsuzaka et al, 2004) and humans (Mayes, 1993;Dirlewanger et al, 2000;Stanhope et al, 2009). In addition, the rapid metabolism of fructose and the activation of energy-demanding processes increase the adenosine monophosphate (AMP):ATP ratio (Leclerc et al, 1998;Muoio et al, 1999;Cha et al, 2008).…”
Section: Fructose and Metabolic Flexibilitymentioning
confidence: 99%